Commodity Prices, Exchange Rate Fluctuation and Sustainable Development Goals in Sub-Saharan Africa: An Empirical Investigation - Asuquo, Eyo (Graduate School of Business (GSB), 2022)
This dissertation examines the impact of commodity price change and exchange rate fluctuations on the capacity of Sub-Saharan African (SSA) countries to attain the UN 2030 agenda on sustainable development by using the dynamic panel data of forty-five (45) countries in Sub-Saharan Africa over a twenty-year timeframe (1999–2018). The study used the commodity terms of the trade index to measure commodity price behaviour, the real effective exchange rate index to measure bilateral exchange rate behaviour and lastly, human development index was used as a measure of human development outcomes that are consistent with the 17 SDG targets. The following control variables were included in the model specification: financial development index (a measure of resource allocation efficiency), external financial flow (a measure of foreign exchange flow) and governance indicators (a measure of institutional quality). Furthermore, the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) modeling technique was used in predicting annual volatilities for commodity terms of trade and real effective exchange rate. The generated data was included in the panel data set and the Generalized Method of Moments (GMM) estimation technique was utilised in estimating the regression model. The main findings of this dissertation are that commodity prices, commodity price volatility and the real effective exchange rate all have a positive and significant correlation with sustainable human development, while the real effective exchange rate volatility has a negative and significant correlation with sustainable human development. Financial development was also observed to have a significant and positive effect on sustainable human development, whereas external financial flow and governance quality were found to have an inverse relationship with sustainable human development. However, further analysis of the regression result reveals the presence of ‘resource curse' amongst SSA countries. This can be ascribed to the consistent declining trend in the region's commodity terms of trade and a corresponding decline in the human development index. This situation is simply reminiscent of the need to transform the resource-dependence profile of SSA through the implementation of intuitive policies and strategies that will promote the efficient utilisation of primary commodities to improve the wellbeing of the populace. Hence, focusing on economic diversification, industrialisation of the commodity sector, building quality institutions and better management of the economy should be of greater concern towards the attainment of Sustainable Development Goals rather than depend on foreign aids.